PENGARUH REBUSAN DAUN BINAHONG (Anredera cordifolia) TERHADAP KUALITAS SPERMATOZOA MENCIT (Mus musculus L.) DIABETES (BIOPROSPEK: Jurnal Ilmiah Biologi, 2018)
This research aimed to evaluate the effect of decoction of the leaves binahong in improving of sperm quality of diabetic mice induced by alloxan. The quality of mice sperm including number of spermatozoa, motility and morphology of spermatozoa were determined after 30 days. Completed randomized design was use in this research, 30 mice were devided randomly into 5 groups (negative control, positive control, first treatment dose of 29 mg, 57 mg doses of treatment II and 114 mg doses of treatment III). The results of the quality of spermatozoa were presented as mean ± standar error (SE). Analysis of Variances (ANOVA) was used to determined statistical different among the group, followed by Duncan Multiple Range Test (DMRT) with significant level 95%. The results found that there was an increase in blood sugar levels followed by a decline in the number of spermatozoa, motility of spermatozoa (P>0,05) and the increase in abnormal morphology of spermatozoa (P